2015
DOI: 10.1128/iai.00140-15
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Models for Bubonic Plague Reveals Unique Pathogen Adaptations to the Dermis

Abstract: H ost-pathogen interactions begin with transmission and continue as the pathogen disseminates into deeper tissues. These tissues are in themselves microenvironments with defined immunological characteristics and can serve as barriers to prevent spread. For arthropod-borne pathogens, the skin epithelium is the first barrier that must be surpassed to penetrate into deeper organs (1, 2). The complexity of the immune responses of each layer of the skin reflects the specificity at which this tissue can act upon inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 32 publications
0
20
0
Order By: Relevance
“…Recently, it was reported that intradermal inoculation of Y. pestis in C57BL/6J mice resulted in faster kinetics of infection compared to that of the subcutaneous route of inoculation due to the organisms' greater ability to access the vascular and lymphatic vessels in the dermis (69). Studies have shown that the dermis of the skin is enriched in terminal lymphatic vessels, which facilitate antigen uptake and the infiltration of immune cells to mount a stronger immune response compared to that of the subcutaneous layer (70)(71)(72).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was reported that intradermal inoculation of Y. pestis in C57BL/6J mice resulted in faster kinetics of infection compared to that of the subcutaneous route of inoculation due to the organisms' greater ability to access the vascular and lymphatic vessels in the dermis (69). Studies have shown that the dermis of the skin is enriched in terminal lymphatic vessels, which facilitate antigen uptake and the infiltration of immune cells to mount a stronger immune response compared to that of the subcutaneous layer (70)(71)(72).…”
Section: Discussionmentioning
confidence: 99%
“…Infected fleas deposit bacteria in the dermal layer of the skin while obtaining a blood meal [3]. The bacterial population inoculated in the dermis can be divided into two: a large population that remains in the skin, and a very small population that leaves this tissue [4].…”
Section: Escape From the Skin And Initiation Of Infectionmentioning
confidence: 99%
“…The bacteria that remain in the skin trigger the recruitment of neutrophils [46], which can be seen in close proximity to the bacteria or engulfing them. Neutrophils arrest bacterial proliferation in the skin but are unable to clear infection in this tissue [3, 4]. Accordingly, Y. pestis must interfere, at least to some extent, with the normal function of neutrophils.…”
Section: Escape From the Skin And Initiation Of Infectionmentioning
confidence: 99%
See 2 more Smart Citations